Pembentukan Identitas Sosial Perempuan Bekerja Dalam Komunitas Perempuan Kajian Atas Reputasi, Dukungan Sosial, dan Ketahanan Ekonomi Keluarga - Rahajeng Puspitosari (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to examine the process of social identity formation among working women within women's communities by exploring the roles of reputation, social support, and family economic resilience. A qualitative approach with a case study design was employed to gain an in-depth understanding of women's experiences in constructing their social identity through active participation in community activities. Informants were selected using purposive sampling and included working women, community leaders, and supporting informants. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing and verification. Data trustworthiness was ensured through source triangulation, method triangulation, time triangulation, and member checking. The findings reveal that reputation functions as symbolic capital that fosters recognition and trust within the community. Social support strengthens women's sense of belonging, solidarity, and self-confidence through emotional, informational, and instrumental interactions. Furthermore, participation in women's communities enhances women's economic capabilities, thereby reinforcing family economic resilience and expanding their roles in household decision-making. These three dimensions interact dynamically to shape a stronger, more adaptive, and empowered social identity among working women. This study contributes theoretically by extending the application of Social Identity Theory within the context of women's communities. Practically, the findings provide insights for policymakers and community organizations in designing women's empowerment programs that emphasize reputation building, social support, and family economic resilience.